Infertility case presentation in Zinner syndrome: Can a long‐lasting seminal tract obstruction cause secretory testicular injury?. (7th October 2019) - Cito, Gianmartin; Sforza, Simone; Gemma, Luca; Cocci, Andrea; Di Maida, Fabrizio; Dabizzi, Sara; Natali, Alessandro; Minervini, Andrea; Carini, Marco; Masieri, Lorenzo
Abstract: Zinner syndrome (ZS) could represent an uncommon cause of male infertility, as result of the ejaculatory duct block, which typically leads to low seminal volume and azoospermia. A 27‐year‐old Caucasian man reported persistent events of scrotal‐perineal pain and dysuria during the past 6 months. The andrological examination showed testicular volume of 10 ml bilaterally. Follicle‐stimulating hormone was 32.0 IU/L, luteinising hormone was 16.3 IU/L, total testosterone was 9.0 nmol/L, and 17‐beta‐oestradiol was 0.12 nmol/L. The semen analysis revealed absolute azoospermia, semen volume of 0.6 ml and semen pH of 7.6. The abdominal contrast‐enhanced computed tomography showed (a) left kidney agenesis; (b) an ovaliform hypodense mass of 65 × 46 millimetres with fluid content, which was shaping the bladder and the left paramedian prostatic region, compatible with a left seminal vesicle pseudocyst; and (c) an enlargement of the right seminal vesicle. The patient was diagnosed with ZS, and he was scheduled for robot‐assisted laparoscopic left vesiculectomy. Subsequently, testis biopsy was characterised by complete germ cell aplasia. The onset symptomatology is often blurred and difficult to detect. It is important to diagnose and manage early this condition, because a long‐lasting seminal tract obstruction could determine an irreversible secretory testicular injury.